XRF core scanning results of Core LU18-2 - Valentin Nigg; Paola Bacigaluppi; David F Vetsch; Hendrik Vogel; Katrina Kremer; Flavio S Anselmetti (PANGAEA, 2021)
Results of the XRF core scanning of sediment core LU18-2. Measurements were performed using an ITRAX-XRF core scanner (Cox Ltd., Sweden) equipped with a Cr-tube set to 30 kV and 50 mA at the Institute of Geological Sciences, University of Bern.
In: Nigg, V et al. (2021): Shallow-Water Tsunami Deposits: Evidence from Sediment Cores and Wave Propagation of the 1601 CE Lake Lucerne Event [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938716